Diving by wintering puddle ducks - Bourget, Andr; Chapdelaine, Gilles (Wildfowl, 1975)
Observation of foraging dives by Black Ducks Anas rubripes, Mallard A. platyrhynchos and Pintail A. acuta, were made during the 1973-1974 winter near Montreal, Quebec. Mean duration diving times from Pintail (5.4 sec) and Mallard (5.2 sec) were significantly longer than for the Black Duck (4.9 sec). This type of feeding behaviour by puddle ducks followed temporary loss of shallow-water feeding areas during cold spells.